Intraoperative care to avoid precipitation of serotonin syndrome in an at-risk adolescent presenting for posterior spinal fusion. - A. Elhamrawy; J. D. Tobias (Pediatric Anesthesia and Critical Care Journal, 2023)
Serotonin syndrome is an uncommon adverse reaction as- sociated with specific psychotropic and serotonin en- hancing medications. It can be precipitated by blockade of the extracellular clearance of serotonin or its increased release from serotonergic neurons. Clinical features in- clude autonomic signs, neuromuscular changes, and al- tered mental status with life-threating complications in- cluding hemodynamic instability, hyperthermia, muscle rigidity, and rhabdomyolysis. Given the multiple medi- cations used during the perioperative period, there are nu- merous anecdotal reports of serotonin syndrome presenting during perioperative care. We present an ad- olescent who required anesthetic care during posterior spinal fusion. She was at risk for serotonin syndrome due to the potential interaction of prescription, over-the-coun- ter, and anesthetic medications. The etiology, presenta- tion, and treatment of serotonin syndrome are presented. Previous reports of serotonin syndrome during anesthetic care are reviewed and interventions to prevent its periop- erative occurrence presented.